2021
DOI: 10.1155/2021/6670064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Zip-Type Skin Closure Device and Staple for Total Knee Arthroplasty: A Meta-Analysis

Abstract: Purpose. To compare the efficacy and safety of zip-type skin closure device (SCD) and staple in total knee arthroplasty (TKA). Methods. Potential academic articles were identified from PubMed, Springer, ScienceDirect, and Cochrane Library from the inception of electronic databases to July 2020. The statistical analyses were performed with RevMan 5.1. Results. One randomized controlled trial (RCT) and 5 non-RCTs met the inclusion criteria. Present meta-analysis reveals that SCD is associated with lower wound pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Medizip (Nycomed Pharma GmbH, Ismaning, Germany) was evaluated in 12 patients in the early 2000s by Bastian et al 25 The target wound was a low midline abdominal wound with a median length of 17.17 cm (range 15. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] resulting from an open prostatectomy. Wound dehiscence (2-3 mm) was detected in two patients and one blister beneath the zipper was detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medizip (Nycomed Pharma GmbH, Ismaning, Germany) was evaluated in 12 patients in the early 2000s by Bastian et al 25 The target wound was a low midline abdominal wound with a median length of 17.17 cm (range 15. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] resulting from an open prostatectomy. Wound dehiscence (2-3 mm) was detected in two patients and one blister beneath the zipper was detected.…”
Section: Resultsmentioning
confidence: 99%
“…At 6 weeks, POSAS scores were better for the zip device compared with the scores for staples, including improved colour ( p = 0.021), stiffness ( p = 0.002), thickness ( p = 0.048), vascularity ( p = 0.002), pigmentation ( p = 0.003), thickness ( p = 0.003), relief ( p = 0.001), pliability ( p = 0.005), surface area ( p = 0.002) and observer overall opinion ( p = 0.0004). Tian et al 14 compared zip‐type skin closure with staple closure in a meta‐analysis, which incorporated six studies and 3550 knees undergoing primary TKAs. Zip‐type skin closure devices caused less pain and lowered medical costs compared with staples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might change with the development of novel degradable polyurethane-based tissue sealants [ 26 ]. Numerous reports on wound closure after knee surgery showed that zipper-like devices can produce equal or better results than staples [ 27 ]. Finally, the use in ointments and gels loaded with biomodulatory molecules [ 28 ] is yet to be fully evaluated, but seems to be an option in burns and diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…15 They are safe and effective treatment options and have been adopted in many practices. [16][17][18] This study was developed to directly compare Zip, Clozex, and a typical closure method using a running 3-0 Prolene suture and to determine which provides the best cosmetic result using the Stony Brook Scar Evaluation Scale (SBSES). 1,19 Secondary outcomes included an assessment of surgeon satisfaction with the closure method, incidence of complications, and cost of each closure method taking into consideration both the direct expense of the devices and their indirect costs (ie, time to apply and expense of surgical room utilization).…”
mentioning
confidence: 99%